'...for all values of x'??? (1 Viewer)

Joined
May 2, 2024
Messages
63
Gender
Male
HSC
2025
u can format it like this:

RTP: f(x)=f(-x)

LHS = f(x)
= x^4 + 2x^2 + 3

RHS = f(-x)
= (-x)^4 + 2(-x)^2 + 3
= x^4 + 2x^2 + 3
= LHS .•. f(x)=f(-x)
 

C2H6O

Well-Known Member
Joined
Oct 18, 2024
Messages
257
Gender
Male
HSC
2025
yes i know how to solve it i just dont know what was meant by 'all values of x' like do i sub in a variable to prove changing x will still prove f(x)=f(-x)
Idk if you already know what it means now, but just in case: by subbing in x (or -x) and treating it normally to complete the proof, you will have automatically solved for every number (bc x could be every number)
 

Users Who Are Viewing This Thread (Users: 0, Guests: 1)

Top